"Conservation, Tradition and Popular Iconoclasm in North America". (2nd January 2021) - Kapp, Paul Hardin
ABSTRACT: Throughout North America, contentious debates and protests are occurring over the existence of historic monuments that represent racial hatred. As post-colonial countries, the United States and Canada, are only now grappling with managing historic statues, buildings, and landscapes associated with African American racism and cultural genocide among aboriginal people. The "negative heritage" embedded in these monuments was created by acts of tradition. In this context, tradition is a series of acts and rituals intended to embed cultural values on a place or an object. As North Americans acknowledge the injustice that was done to African Americans and aboriginal people, an iconoclastic movement is underway, resulting in the removal of monuments and buildings. This paper proposes that the role of tradition and iconography should be re-examined in conserving and managing North American built patrimony. Tradition, by its nature, is an intangible heritage and new traditions can transform people's perceptions of historic monuments. Using the "Blood Swept Lands and Seas of Red" installation at the Tower of London as a case study, this article will explore how using tradition can redefine a historic monument within the context of contemporary time and place.